Insignificance: On the Unobtrusiveness of Material Things. Issue 1 (February 2020) - Thomas, Julian
Abstract : In their introduction to the discussion of Beiläufigkeit in archaeology, Pollock, Bernbeck, Appel, Loy and Schreiber build pleasingly on the theme of what Daniel Miller refers to as the 'humility' of physical things (2010, 50). By this he means that objects do not determine or prescribe the actions of human beings, but mutely establish the circumstances under which we operate, conditioning our expectations of how to proceed. Things are often not conspicuously meaningful, but unobtrusive or 'hiding in plain sight' and bringing about unacknowledged effects (Alvis 2017, 212). This state of affairs has been recognized by both the phenomenological tradition and the more recent 'new materialisms', but what I want to suggest in this contribution is that these perspectives implicitly indicate that things can be 'incidental' in a variety of subtly different ways.